Lightlark eaudiobook - Aster, Alex (Lightlark, 2022)
WELCOME TO THE CENTENNIAL Every hundred years, the island of Lightlark appears for only one hundred days to host a deadly game, where the rulers of six realms fight to break their curses and win unparalleled power. Each ruler has something to hide. Each curse is uniquely wicked. To break them—and save themselves and their realms—one ruler will die. To survive, Isla Crown must LIE. CHEAT. BETRAY. Even as love complicates everything ...